Proceedings of the 26th Conference on User Modeling, Adaptation and Personalization 2018
DOI: 10.1145/3209219.3209248
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Users' Personality from Instagram Pictures

Abstract: Instagram is a popular social networking application that allows users to express themselves through the uploaded content and the different filters they can apply. In this study we look at personality prediction from Instagram picture features. We explore two different features that can be extracted from pictures: 1) visual features (e.g., hue, valence, saturation), and 2) content features (i.e., the content of the pictures). To collect data, we conducted an online survey where we asked participants to fill in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 25 publications
3
27
0
3
Order By: Relevance
“…Out of the three tested classifiers, we found that the RBF network performs best across the classifiers that were used. This seems to be in line with findings of prior work that tested multiple classifiers as well (e.g., [4,6]). The RBF network has shown to perform well on smaller datasets that are similar in size as used in the current work.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Out of the three tested classifiers, we found that the RBF network performs best across the classifiers that were used. This seems to be in line with findings of prior work that tested multiple classifiers as well (e.g., [4,6]). The RBF network has shown to perform well on smaller datasets that are similar in size as used in the current work.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Although the overall performance between different datasets differ, similar trends can be observed on the predictability of each personality trait. The performance of the current dataset does not reach the levels of other datasets, but similar trends are observable Table 4: Comparison of personality prediction compared to prior work on Instagram [6], Facebook [4], and Twitter [17] that are using a similar performance measurement. Root-mean-square error (RMSE) is reported (r ∈ [1,5]) to indicate prediction performance of the personality traits: (O)penness to experience, (C)onscientiousness, (E)xtraversion, (A)greeableness, (N)euroticism.…”
Section: Comparison With Other Predictive Modelsmentioning
confidence: 64%
See 3 more Smart Citations